THE INITIATION, RESPONSE, AND FEEDBACK (IRF) IN ENGLISH LANGUAGE TEACHING: A LITERATURE REVIEW - Dalia, Arisa Cahyalaili; Putra, Fahry Rizaldy (Jurnal Ilmiah Spectral, 2024)
Initiation between teachers and students is the foundation for classroom discourse. Multiple models for classroom discourse could improve the initiation between the teacher and students in the classroom. It is presumptively true that classroom discourse "follows a fairly normal and predictable pattern, also known as IRF, or IRE: Initiation, Response, and Feedback or Evaluation, consists of three parts: a teacher Initiation, a student response, and a teacher Feedback. Some authors and practitioners prefer IRE to represent that teachers' feedback is typically an assessment of a student's participation. Teachers continually evaluate if a statement is correct and provide feedback to students. In this study, researchers use a literature review. A literature review examines academic books, papers, and other sources relevant to a topic, discipline of study, or theory. The study employs reliable sources from articles and e-books. This paper explores the Initiation, Response, and Feedback in English language teaching.